A Miniaturized Magnetic Induction Sensor Using Geomagnetism for Turn Count of Small-Caliber Ammunition - Jong-Soo Oh; Young-Ho Lee; Seok-Woo Lee; Sang-Hee Yoon (Sensors, 2006)
This paper presents a miniaturized magnetic induction sensor (MMIS), wheregeomagnetism and high rpm rotation of ammunition are used to detect the turn number ofthe ammunition for applications to small-caliber turn-counting fuzes. The MMIS, composedof cores and a coil, has a robust structure without moving parts to increase the shocksurvivability in a gunfire environment of ~30,000 g’s. The MMIS is designed and fabricatedon the basis of the simulation results of an electromagnetic analysis tool, Maxwell® 3D. Inthe experimental study, static MMIS test using a solenoid-coil apparatus and dynamicMMIS test (firing test) have been made. The present MMIS has shown that an inductionvoltage of 6.5 mVp-p is generated at a magnetic flux density of 0.05 mT and a rotationalvelocity of 30,000 rpm. From the measured signal, MMIS has shown a signal-to-noise ratioof 44.0 dB, a nonlinearity of 0.59%, a frequency-normalized sensitivity of 0.256±0.010V/T·Hz and a drift of 0.27% in the temperature range of -30~ 43°C. Firing test has shownthat the MMIS can be used as a turn-counting sensor for small-caliber ammunition,verifying the shock survivability of the MMIS in a high-g environment.